A New Glider-Compatible Optical Sensor for Dissolved Organic Matter Measurements: Test Case from the NW Mediterranean Sea - Cyr, Frédéric; Tedetti, Marc; Besson, Florent; Beguery, Laurent; Doglioli, Andrea M.; Petrenko, Anne A.; Goutx, Madeleine (Frontiers in Marine Science, 2017)
The MiniFluo-UV is a new glider-compatible optical sensor for measurements of dissolved organic matter (DOM) in natural waters. The working principle, sensor design and challenges faced during the validation phase are reported. The first in situ application of the sensor during three glider deployments in the NW Mediterranean sea (spring, summer and fall) are also presented. For these campaigns, the two channels of the sensor were adjusted to target Tryptophan-like (excitation/emission wavelengths: 275/340 nm) and Phenanthrene-like (255/360 nm) fluorescence. These were chosen because they represent fluorophores of interest commonly found in seawater. While Tryptophan (an amino-acid believed to be a by-product of biological activity) is naturally found in the ocean, Phenanthrene (a polycyclic aromatic hydrocarbon) is mainly introduced in the environment via human activities. The addition of these variables to more common physical and biogeochemical glider measurements reveals new features of DOM dynamics in the Mediterranean Sea. For example, the temporal and spatial decoupling between Tryptophan-like and Chl-$a$ fluorescence suggests that the former is not only a marker of biological activity, but could also give more subtle information on the microbial processes occurring. The identification of a Phenanthrene-like layer just below the pycnocline at all seasons also raises questions on the mechanisms driving its presence in the Mediterranean. Knowing that the role of ocean DOM on atmospheric carbon sequestration is becoming clearer, the high spatio-temporal resolution possible with this new sampling strategy may represents a key step towards our deep understanding of DOM dynamics and its role on the biological pump.